EFFICIENCY AND SAFETY OF TOURNIQUET DURING TOTAL KNEE ARTHROPLASTY: WHEN TO PERFORM RELEASE? - D. V. Chugaev; N. N. Kornilov; P. G. Kogan (Travmatologiâ i Ortopediâ Rossii, 2017)
Use of a pneumatic tourniquet during total knee arthroplasty is an effective option allowing reduction of the time of surgery and intraoperative blood loss. At the same time, there are a lot of researchers who advocate differing tactical approaches to the duration of the tourniquet application — the so-called “early” and “late” releases.Purpose of the study. To assess the effectiveness and safety of various methods of tourniquet use during primary total knee arthroplasty.Material and methods. 72 patients with end-stage knee osteoarthritis were randomly divided into two equal prospective groups: 1) keeping the tourniquet throughout the surgery, including wound closure (late release); 2) performing knee arthroplasty using the tourniquet until after implantation of the prosthesis component and implementation of hemostasis after the release of the tourniquet (early release). Such aspects as perioperative blood loss and changes in blood counts, blood transfusion volume, and severity of pain on the VAS scale, the rate of recovery of the knee joint function and number of postoperative complications were assessed during hospital stay of patients.Results. The duration of procedures was 70±15,4 min for the Group I with tourniquet throughout surgery (late release) and 95±27,5 for the Group II with early release (p = 0,001). On the 7th day after the arthroplasty the authors observed statistically significant differences (p<0,05) in the dynamics of reducing the level of hemoglobin, red blood cells and hematocrit in patients of compared groups — in patients who underwent late release of the tourniquet, these indicators were higher. When assessing the rate of recovery of knee joint function according to the KSS -and the intensity of the pain syndrome no significant statistical differences were found in the patients of both groups.Conclusion. Application of the tourniquet throughout the surgery to release after closure of the surgical wound does not lead to a sharp increase in the number of ischemic and thromboembolic complications, while at the same time, the application of this methodology to a large extent maintains hemoglobin indicators, red blood cells and hematocrit at a high level without a critical decrease.